The Effect of Mothers’ Knowledge and Attitudes on Practices Regarding Infant and Young Child Feeding: A Cross-Sectional Analysis at Child Welfare Clinics in Kiambu County, Kenya - Ahmed, Tasneem (Amref International University, 2025)
Background: Optimal Infant and Young Child Feeding (IYCF) practices are essential for preventing malnutrition and child mortality, particularly during the first 1,000 days. In Kenya, poor IYCF practices remain a major contributor to child undernutrition. Objective: To assess the knowledge, attitudes, and practices (KAP) related to IYCF among mothers of children aged 6–23 months across rural, urban, and slum settings in Kiambu County. Methods: This study employed a facility-based, comparative cross-sectional study design across two purposively selected Child Welfare Clinics (CWC’s): Wangige Subcounty Hospital and Kiandutu Health Centre. The study recruited 354 mothers of children aged 6–23 months. Data were collected using structured questionnaires via KoboCollect assessing maternal IYCF knowledge, attitudes, and practices (KAP). All data were analysed using STATA software (version 14, StataCorp). Results: Of the 354 mother–child pairs, 67.2% had adequate IYCF knowledge, yet only 7.9% knew the recommended complementary feeding frequency. While 96.9% reported positive attitudes, 23% supported early complementary feeding and 17% avoided colostrum. Overall, 73.2% practiced adequate IYCF, though dietary diversity remained low (57.6%) and protein intake limited (meat/fish: 16.4%). Facility-level differences outweighed residential effects, with attendees of Wangige Health Centre demonstrating better practices than those at Kiandutu (78.2% vs. 68.0%, p = 0.030). Slum areas showed the strongest knowledge practice association (+28.8%, p = 0.002), while rural areas demonstrated attitude driven patterns (p = 0.018). Conclusion: Critical gaps were identified between IYCF knowledge and its implementation, particularly regarding complementary feeding. Marked facility-level variations pointed to inconsistencies in service quality. Notably, higher maternal education emerged as a strong and consistent predictor of appropriate IYCF practice adoption, alongside caregiving experience. These findings underscore the importance of educational empowerment and advocate for a shift from passive information-sharing to tailored, competency-based interventions that reflect the diverse socio-economic realities of rural, slum, and urban settings.
A Research Thesis Submitted to The Departmet of Community Health, School of Public Health in Partial Fulfilment of The Requirements for the Award of the Degree of Master of Public Health (Public Health Nutrition) at Amref International University